2014
DOI: 10.1073/pnas.1405641111
|View full text |Cite
|
Sign up to set email alerts
|

Syntrophic exchange in synthetic microbial communities

Abstract: Metabolic crossfeeding is an important process that can broadly shape microbial communities. However, little is known about specific crossfeeding principles that drive the formation and maintenance of individuals within a mixed population. Here, we devised a series of synthetic syntrophic communities to probe the complex interactions underlying metabolic exchange of amino acids. We experimentally analyzed multimember, multidimensional communities of Escherichia coli of increasing sophistication to assess the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
549
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 505 publications
(569 citation statements)
references
References 40 publications
20
549
0
Order By: Relevance
“…Development of an ecological model capable of predicting coculture behavior Mathematical modeling of synthetic communities is a powerful tool for generating experimentallytestable predictions of what controls mutualism dynamics and stability (Klitgord and Segrè, 2010;Mee et al, 2014;Zomorrodi and Segrè, 2015;Zelezniak et al, 2015). We therefore developed an ecological model (Figure 4) based on previously described interactions for mutualistic systems with Monod uptake kinetics (Meyer et al, 1975;Lee et al, 1976).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Development of an ecological model capable of predicting coculture behavior Mathematical modeling of synthetic communities is a powerful tool for generating experimentallytestable predictions of what controls mutualism dynamics and stability (Klitgord and Segrè, 2010;Mee et al, 2014;Zomorrodi and Segrè, 2015;Zelezniak et al, 2015). We therefore developed an ecological model (Figure 4) based on previously described interactions for mutualistic systems with Monod uptake kinetics (Meyer et al, 1975;Lee et al, 1976).…”
Section: Resultsmentioning
confidence: 99%
“…As an alternative, synthetic microbial communities (cocultures) have been developed in which two or more species are cultivated together under laboratory conditions. Cocultures preserve core aspects of natural systems while offering greater practical experimental control (Shou et al, 2007;Hillesland and Stahl, 2010;Summers et al, 2010;Harcombe, 2010;Momeni et al, 2011;Hom and Murray, 2014;Mee et al, 2014). They are also more amenable to modeling than are natural systems and facilitate the development, experimental testing and refining of models for predicting community behavior (Zomorrodi and Segrè, 2015;Johns et al, 2016;Lindemann et al, 2016;Widder et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, many of the amino acids and vitamins Ca. U copiosus appears unable to synthesize are involved in synergistic growth 47 and may be supplied by other microbes as common community goods 48 . Based on the few spartobacterial isolates that have been cultivated 11 , culture-independent studies 10,49 and the genomic data presented here, we speculate that Ca.…”
Section: Lifestyles (Supplementarymentioning
confidence: 99%
“…So far, the majority of studies of microbial mutualisms have focused on cross-feeding, the mutually beneficial exchange of metabolites (10)(11)(12)(13)(14)(15)). Studies involving cross-feeding amino acid auxotrophs (10)(11)(12) found that the division of labor within the mutualism can increase the fitness of cross-feeding cocultures compared with a self-sufficient strain (10). The greatest gains seem to emerge when amino acids are costly to produce (11).…”
mentioning
confidence: 99%
“…Studies involving cross-feeding amino acid auxotrophs (10)(11)(12) found that the division of labor within the mutualism can increase the fitness of cross-feeding cocultures compared with a self-sufficient strain (10). The greatest gains seem to emerge when amino acids are costly to produce (11). These mutualisms can even form immediately when complementary strains encounter each other and without a period of coevolution, although allowing time for adaptation may increase their resilience (12).…”
mentioning
confidence: 99%